Computational Systems Pharmacology and Molecular Docking Reveal an Anti-Apoptosis and Anti-Inflammatory Mechanism of Compound Angelica Ligusticum Wallichii Granules in the Treatment of Endometriosis - Li Y; Zhu J; Tang J (Drug Design, Development and Therapy, 2023)
Yueyan Li, Jialei Zhu, Jing Tang Department of Pharmacy, Obstetrics and Gynecology Hospital of Fudan University, Shanghai, 200090, People’s Republic of ChinaCorrespondence: Jing Tang, Department of Pharmacy, Obstetrics and Gynecology hospital of Fudan University, 128 Shenyang Road, Yangpu District, Shanghai, 200090, People’s Republic of China, Tel/Fax +86 21 33180593, Email 1817@fckyy.org.cnBackground: Traditional medicine is a common treatment option for endometrioid-related symptoms. In the past few decades, Guixiong Xiaoyi formula has been widely used as a traditional medicine for the treatment of endometriosis.Purpose: This study aimed to prepare compound Angelica Ligusticum wallichii granule (CALG) by modern technological methods and to study its pharmacodynamics and mechanisms of treating endometriosis.Methods: The ingredients of CALG were determined by UPLC-Q-TOF/MS. Target prediction of compounds and diseases was performed using databases, and the mechanisms of CALG were predicted by Gene Ontology and Kyoto Encyclopedia of Genes and Genomes and verified by molecular docking. Furthermore, a rat model of endometriosis was established to study the effects of CALG on endometriosis in vivo.Results: CALG with good specificity, durability, and stability was obtained following a detailed preparation process and quality control standard. Using network systems pharmacology, 109 chemical compositions and 104 core targets were identified for the treatment of endometriosis. The composition-target-channel-disease network topology analysis of the top 15 chemical compositions of CALG showed that the beneficial effect of CALG on endometriosis was attributed to phenolic compounds. In addition, CALG treatment reduced the volume of ectopic uterine lesions, promoted apoptosis, inhibited the secretion of inflammatory cytokines, and increased HIF-1 expression in rats with endometriosis.Conclusion: CALG induces apoptosis and inhibits inflammation and is a promising drug for the treatment of endometriosis.Graphical Abstract: Keywords: endometriosis, Angelica Ligusticum wallichii granule, network systems pharmacology, molecular docking, traditional Chinese medicine